The measurement properties of pediatric observational pain scales: A systematic review of reviews. (August 2017) - Andersen, Randi Dovland; Langius-Eklöf, Ann; Nakstad, Britt; Bernklev, Tomm; Jylli, Leena
Abstract: Background: Valid observational pain scales are needed to assess pain and ensure sufficient treatment of pain in children that lack the verbal ability to self-report pain. Published reviews attempt to synthesize results from primary studies validating these scales and based on the findings recommendations may be given, for example which pain scales are the most appropriate for use in different pediatric populations. Objectives: The aims of this review were to describe how systematic reviews have evaluated and recommended observational pain scales for use in children aged 0–18 years and appraise the evidence underlying these recommendations. Design: Systematic review of reviews. Data sources: The Cochrane Library, PubMed/MEDLINE, CINAHL, Web of Science, and PsychINFO were searched from inception to September 2016. Reference lists and gray literature were searched for additional studies. Review methods: Study selection and data extraction were performed by two reviewers independently with a disagreement procedure in place. Methodological quality or study validity was measured using the Assessment of Multiple Systematic Reviews checklist and risk of bias or internal validity was measured using the Risk of Bias in Systematic Reviews tool. The review protocol was registered with PROSPERO: registration number CRD42016035264. Results: Twelve reviews met the inclusion criteria. Together; they included 65 different observational pain scales for use in children, of which 28 were recommended at least once. Face, Legs, Activity, Cry, Consolability/revised version of Face, Legs, Activity, Cry, Consolability, COMFORT/COMFORT behavioral scale and Children's Hospital of Eastern Ontario Pain Scale were evaluated and recommended most frequently. Few of the included reviews assessed the methodological quality of the studies included in the review. The narrative analysis consisted mostly of a reiteration of the results from the primary studies. In general, more recent reviews showed a lower risk of bias than older ones. Conclusions: Included reviews exhibited low quality of evidence; thus, their recommendations regarding pain scales for use in clinical practice or research with children that lack the verbal ability to self-report pain should be interpreted with caution.